Exploring Racism and Health: An Intensive Interactive Session for Medical Students - Michelle DallaPiazza; Mercedes Padilla-Register; Megana Dwarakanath; Elyon Obamedo; James Hill; Maria L. Soto-Greene (Association of American Medical Colleges, 2018)
Introduction Growing recognition of the deleterious effects of racism on health has led to calls for increased education on racism for health care professionals. As part of a larger curriculum on health equity and social justice, we developed a new educational session on racism for first-year medical students consisting of a lecture followed by a case-based small-group discussion. Methods Over the academic years of 2016-2017, 2017-2018, and 2018-2019, a total of 536 first-year medical students participated in this mandatory session. The course materials were developed as a collaboration between faculty and students. The lecture was delivered in a large-group format; the small-group case-based discussion consisted of 10-12 students with one upper-level student facilitator. Results The majority of respondents for the course evaluation felt that the course had met its stated objectives, and many commented that they had an increased awareness of the role of racism in shaping health. Students felt that the small-group activity was especially powerful for learning about racism. Discussion Active student involvement in curriculum development and small-group facilitation was critical for successful buy-in from students. Additional content on bias, stereotyping, and health care disparities will be the focus of faculty development programs and will also be integrated into the clerkships to build on these important topics as students are immersed in clinical care.